The Effect of Steaming Time on the Chemical and Organoleptic Characteristics of Kepok Banana Tape (Musa paradisiaca Linn) - Siti Nuryanti; Olivia Inrawati I. Somang; Tahril; Arwansyah (Jurnal Penelitian Pendidikan IPA, 2025)
Steaming is a very important factor in the processing of food ingredients, especially kepok bananas before being fermented into tape. This study was to determine the effect of steaming time on the quality of kepok banana tape seen from the chemical characteristics including pH value determined using a pH meter, sugar content with the phenol sulfate method, alcohol content with the acid-base titration method, and organoleptic testing by 15 panelists. The bananas used were half-ripe kepok bananas from Dolo District, Sigi Regency, with variations in steaming time of 25, 30 and 35 minutes. The results showed that kepok banana tape with a steaming time of 25 minutes had a pH of 4.88; sugar content 12.62%; alcohol content 1.47%; color preference 3.4; aroma 2.8; texture 3.6 and taste 2.8. Tape with a steaming time of 30 minutes had a pH of 4.85; sugar content 16.37%; alcohol content 1.52%; color preference 3.5; aroma 2.6; texture 3.2; and taste 3.1. And tape with a steaming time of 35 minutes has a pH of 4.85; sugar content 10.57%; alcohol content 1.61%; color preference 3.4; aroma 3; texture 3.4; and taste 3.4. Based on the results of chemical and organoleptic characteristic tests, the best quality of banana kepok tape is tape with a steaming time of 35 minutes. This study provides educational relevance by illustrating the application of chemistry concepts such as acid-base reactions, fermentation, and analytical techniques in real-world food processing, making it a potential contextual learning material in science education.